Enhanced Services for the Hard-to-Employ Center for Employment Opportunities (CEO), New York City - Redcross, Cindy ([Verlag nicht ermittelbar], 2012)
The Enhanced Services for the Hard-to-Employ (HtE) Demonstration and Evaluation Project was a 10-year study (taken on by the MDRC) that evaluated innovative strategies aimed at improving employment and other outcomes for groups who faced serious barriers to employment. The Enhanced Services for the Hard-to-Employ is the first comprehensive attempt to understand the diverse low-income population and to test interventions aimed at the most common barriers that are encountered in this population's employment. The HtE demonstration was designed to evaluate a variety of innovative ways to boost employment, reduce welfare receipt, and promote well-being in low-income populations. This study evaluated the effectiveness of the Center for Employment Opportunities (CEO), which is an employment program for former prisoners based in New York City. The CEO evaluation aimed to determine whether CEO's transitional jobs and other services are more effective than basic job search assistance. Enrollment for this study was conducted between January 2004 and October 2005 and resulted in a sample of 977 former prisoners (568 in the program group and 409 in the control group). Individuals assigned to the program group were eligible for all of CEO's services, including the pre-employment class, the transitional job, job coaching, job development, a fatherhood program, and post-placement services. Individuals assigned to the control group began with a shorter version of the pre-employment class and were given access to a resource room with basic job search equipment such as computers and fax machines. Evaluation of the CEO program found that the CEO operated as intended and substantially increased employment for the full study sample early in the follow-up period; however, that effect faded over time. The study also found that CEO significantly reduced recidivism, with the most promising impacts occurring among a subgroup of former prisoners who enrolled shortly after release from prison. Among the subgroup that enrolled within three months after release, program group members were less likely than their control group counterparts to be arrested, convicted of a new crime, and reincarcerated. The program's impacts on these outcomes represent reductions in recidivism of 16 percent to 22 percent. In general, CEO's impacts were stronger for those who were more disadvantaged or at higher risk of recidivism when they enrolled in the study. The evaluation of the CEO program included a benefit-cost analysis, which showed that CEO's financial benefits outweighed its costs under a wide range of assumptions. Respondents were asked about their employment history, recidivism history, time spent on parole, parole violations, and arrest history, including prior convictions, types of convictions, and length of incarceration. Information was collected about respondents' work experience with and without the assistance of the CEO; this information included whether respondents participated in group or individual job searches, vocational or educational training, received referrals to job openings, help with their resumes, advice about filing out job applications, job interviews, or how to behave on the job, help with child support issues and whether they participated in father discussion groups or parenting programs. Respondents were also asked about their current living situation, work schedule, hourly wage, job benefits, health coverage, whether they had a mentor, how often they saw their children, and the type of relationship they had with their children. Demographic information includes age, race, marital status, education, employment status, and home ownership status.